2006
DOI: 10.1021/bi060529u
|View full text |Cite
|
Sign up to set email alerts
|

Mac-1 Promotes FcγRIIA-Dependent Cell Spreading and Migration on Immune Complexes

Abstract: The integrin Mac-1 plays a critical role in Fc receptor (FcR)-mediated antibody-dependent cellular cytotoxicity (ADCC). However, the mechanism by which Mac-1 facilitates the functions of FcγRIIA, a major FcR expressed on human leukocytes, is not fully understood. We report here that Mac-1 sustains cell adhesion, enhances cell spreading, and accelerates cell migration on pre-formed immune complexes (ICs) by directly interacting with FcγRIIA but not with the IC substrate. Coupling Mac-1 to FcγRIIA allows FcγRIIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…Moreover, despite several fold higher expression of LFA-1 compared with Mac-1 on monocytes, Mono Mac 6 and THP-1 almost exclusively utilized Mac-1 to adhere to HLA I antibody-stimulated endothelial cells. Finally, there is a well-studied signaling cross-talk between Mac-1 and FcγRs, particularly with FcγRI (72, 81, 82). For these reasons, monocytes may be more responsive to HLA antibody bound on the endothelium compared with other myeloid or lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite several fold higher expression of LFA-1 compared with Mac-1 on monocytes, Mono Mac 6 and THP-1 almost exclusively utilized Mac-1 to adhere to HLA I antibody-stimulated endothelial cells. Finally, there is a well-studied signaling cross-talk between Mac-1 and FcγRs, particularly with FcγRI (72, 81, 82). For these reasons, monocytes may be more responsive to HLA antibody bound on the endothelium compared with other myeloid or lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…FcγRIIA is expressed on neutrophils, eosinophils, macrophages, platelets, and DCs . Physical interaction of Mac‐1 with FcγRIIA by fluorescent resonance energy transfer and co‐immunoprecipitation has been documented . Unexpectedly, this interaction has been found to be via E 252 ‐R 261 in the ligand‐binding I‐domain of Mac‐1 , suggesting an interaction akin to a ligand‐receptor pair.…”
Section: Mac‐1 As a Master Collaborator And Partner In Crimementioning
confidence: 99%
“…Physical interaction of Mac‐1 with FcγRIIA by fluorescent resonance energy transfer and co‐immunoprecipitation has been documented . Unexpectedly, this interaction has been found to be via E 252 ‐R 261 in the ligand‐binding I‐domain of Mac‐1 , suggesting an interaction akin to a ligand‐receptor pair. Functional interaction of FcγRIIA and Mac‐1 has been shown: Transfection of tail‐less FcγRIIA (lacking ITAMs) can phagocytose only when Mac‐1 is cotransfected , and antibody‐dependent cellular cytotoxicity (ADCC) depends on both receptors .…”
Section: Mac‐1 As a Master Collaborator And Partner In Crimementioning
confidence: 99%
“…Also, it has been shown that the integrin Mac-1 interacts directly with FccRIIa and contributes to FccRIIa-mediated sustained cell adhesion, cell spreading, and cell migration on targets covered with immune complexes. These effects likely enhance contact between leukocyte and target, thus favoring effective target cell killing by ADCC or phagocytosis [58]. It has also been reported that FccRIIIb stimulation promotes activation of b1 integrins on human neutrophils [59].…”
Section: Signal Regulators Of Fccrmentioning
confidence: 97%